EFFECT OF USING INSTAGRAM STORIES ON PHUBBING BEHAVIOR IN THE GENERATION Z OF SALATIGA - Lifia Monica Christian, Phang; Daru Purnomo; Dewi Kartika Sari (Profetik: Jurnal Komunikasi, 2020)
Instagram Stories is one of the main features of Instagram. Indonesia becomes one of the most active countries in using and creating Instagram Stories content compared to other countries.  However, the use of the Instagram Stories feature has raised concerns because of the daily activities, such as food consumed, holiday activities, and emotions that become the public consumptions by sharing moments using photos or videos through the Instagram Stories feature. When people use the feature on Instagram Stories to take moments and daily activities, this behavior triggers the ignorance of social interactions surrounding them because they only focus on creating Instagram Stories. The phenomenon of the moments’ preservation through Instagram Stories feature can create phubbing behavior as a definition that describes someone’s indifferent behavior in an environment. They tend to focus on their smartphones rather than interacting with their surroundings. This study was conducted to explore the influence of using Instagram Stories on Generation Z’s phubbing behavior in Salatiga city. It used quantitative methods with the linear regression technique. It used a purposive random sampling technique with 397 respondents as the samples. The result of this study showed that the use of Instagram Stories affects the phubbing behavior in Generation Z in Salatiga, as for the percentage of the influence of the variable use in Instagram Stories toward phubbing behavior is 31.1%. The rest, which is 68.9%, is affected by other factors outside of the use of Instagram Stories that were not conducted by the researchers